Removal of Chromium from Aqueous Solution Using Modified Pomegranate Peel:Mechanistic and Thermodynamic Studies - Tariq S. Najim; Suhad A. Yassin (E-Journal of Chemistry)
Modified pomegranate peel (MPGP) and formaldehyde modified pomegranate peel (FMPGP) were prepared and used as adsorbent for removal of Cr(VI) ions from aqueous solution using batch process. The temperature variation study of adsorption on both adsorbents revealed that the adsorption process is endothermic, from the positive values of ∆H˚. These values lie in the range of physisorption. The negative values of ∆G˚ show the adsorption is favorable and spontaneous. On the other hand, these negative values increases with increase in temperature on both adsorbents, which indicate that the adsorption is preferable at higher temperatures. ∆S˚ values showed that the process is accompanied by increase in disorder and randomness at the solid solution interface due to the reorientation of water molecules and Cr(VI) ions around the adsorbent surface. The endothermic nature of the adsorption was also confirmed from the positive values of activation energy, Ea, the low values of Ea confirm the physisorption mechanism of adsorption. The sticking probability, S*, of Cr(VI) ion on surface of both adsorbents showed that the adsorption is preferable due to low values of S* (0< S* < 1 ), but S* values are lower for FMPGP indicating that the adsorption on FMPGP is more preferable .